2016
DOI: 10.1007/s12155-016-9772-9
|View full text |Cite|
|
Sign up to set email alerts
|

Carbon Inputs from Miscanthus Displace Older Soil Organic Carbon Without Inducing Priming

Abstract: The carbon (C) dynamics of a bioenergy system are key to correctly defining its viability as a sustainable alternative to conventional fossil fuel energy sources. Recent studies have quantified the greenhouse gas mitigation potential of these bioenergy crops, often concluding that C sequestration in soils plays a primary role in offsetting emissions through energy generation. Miscanthus is a particularly promising bioenergy crop and research has shown that soil C stocks can increase by more than 2 t C ha −1 yr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 88 publications
1
11
1
1
Order By: Relevance
“…Activities of peroxidases can be attributed dominantly to soil fungi, and their increase reflects the increase of fungal PLFA. Unlike in the study of Robertson et al [35], soil respiration (Figure 3), referring to the overall activity of the microbial community and degradation of organic matter, increased significantly between first and second year. It may suggest the positive affect of plant growth on microbial activity, likely due to the secretion of root exudates [36].…”
Section: Microbial Communitycontrasting
confidence: 72%
“…Activities of peroxidases can be attributed dominantly to soil fungi, and their increase reflects the increase of fungal PLFA. Unlike in the study of Robertson et al [35], soil respiration (Figure 3), referring to the overall activity of the microbial community and degradation of organic matter, increased significantly between first and second year. It may suggest the positive affect of plant growth on microbial activity, likely due to the secretion of root exudates [36].…”
Section: Microbial Communitycontrasting
confidence: 72%
“…Given a 30% combustion efficiency and 129.2 t ha −1 yield (18 years at Lincolnshire), an increase of 1 t C ha −1 yr −1 in soils would offset 438 g CO 2 ‐eq kWh −1 on a life cycle basis (Eqn , GHG site fixed at −3.66 t CO 2 ‐eq ha −1 yr −1 ). An increase of 1 t C ha −1 yr −1 in the top 30 cm is not unrealistic; at this site, Miscanthus inputs were previously shown to add 0.86 t C ha −1 yr −1 to the top 30 cm (Robertson et al ., ) and Poeplau & Don () saw an average increase of 1.68 ± 0.7 t C ha −1 yr −1 from a range of Miscanthus crops across Europe. The unchanged topsoil C stocks reported here, therefore, have important consequences for whether it is deemed a preferable alternative to conventional fossil fuels.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, despite relatively low yields and a lack of soil C sequestration, the crop studied here had a considerably lower GHG intensity than coal or natural gas when used for electricity generation. Additional research is required to elucidate why soil C stocks are not changing under this plantation (Zatta et al ., ; Robertson et al ., ) and future bioenergy sustainability studies should prioritize land use efficiency over GHG intensity comparisons. Nevertheless, this study demonstrates that even when yields are lower than many other sites due to climate or establishment issues, GHG benefits can still outweigh costs and contribute to climate change mitigation through the provision of low C renewable energy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that Miscanthus lutarioriparius , a C 4 endemic species in central China, can adapt to the semi-arid regions and produce high feedstock in North China [ 18 ]. Furthermore, growing this C 4 grass in the Loess Plateau has many environmental benefits, including soil and water conservation, carbon sequestration and soil restoration in the infertile and soil-eroded region [ 19 21 ]. Thus, bioenergy production in the large scale may bring a sustainable solution to this region [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%